2016
DOI: 10.1002/1873-3468.12351
|View full text |Cite
|
Sign up to set email alerts
|

Host–pathogen interactions of nontypeable Haemophilus influenzae: from commensal to pathogen

Abstract: Nontypeable Haemophilus influenzae (NTHi) is a commensal microbe often isolated from the upper and lower respiratory tract. This bacterial species can cause sinusitis, acute otitis media in preschool children, exacerbations in patients suffering from chronic obstructive pulmonary disease, as well as conjunctivitis and bacteremia. Since the introduction of a vaccine against H. influenzae serotype b in the 1990s, the burden of H. influenzae‐related infections has been increasingly dominated by NTHi. Understandin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(121 citation statements)
references
References 118 publications
0
109
0
Order By: Relevance
“…15 Numerous studies have reported the role of NTHi as cause of mainly noninvasive local infections in children, such as AOM, sinusitis, bronchitis, pneumonia, and conjunctivitis. 6,14,19,20 In particular, AOM infection is commonly caused by NTHi, affecting more than 10% of humans annually worldwide, with 51% of the cases occurring in children younger than 5 years. 6 Moreover, several studies have shown an increased pathogenic potential of NTHi in adults and infants who are susceptible to lung infections, with high case fatality rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Numerous studies have reported the role of NTHi as cause of mainly noninvasive local infections in children, such as AOM, sinusitis, bronchitis, pneumonia, and conjunctivitis. 6,14,19,20 In particular, AOM infection is commonly caused by NTHi, affecting more than 10% of humans annually worldwide, with 51% of the cases occurring in children younger than 5 years. 6 Moreover, several studies have shown an increased pathogenic potential of NTHi in adults and infants who are susceptible to lung infections, with high case fatality rates.…”
Section: Discussionmentioning
confidence: 99%
“…These can cause sinusitis, acute otitis media (AOM), conjunctivitis, and bacteremia in preschool children, and infection in patients suffering from chronic obstructive pulmonary disease. 6 Many studies have reported that NTHi human carriage and disease prevalence has increased, particularly after the introduction of the Hib vaccine. [6][7][8][9] However, there is no such study from Jordan and only few reports from Arab Middle East countries.…”
Section: Introductionmentioning
confidence: 99%
“…Nontypeable Haemophilus influenza (NTHI) infections, in particular newly acquired strains, may trigger infectionrelated exacerbation in COPD and recurrent infections may induce overall disease progression (Duell et al 2016). On using the NTHI strain Rd KW20 isolated from a COPD patient suffering from invasive pneumonia, Wagner et al (2015) noticed strong IL-8 induction in ex vivo infected human lungs; this was reduced in tissue pre-treated with the antiinflammatory drug budenoside.…”
Section: Nontypeable Haemophilus Influenzaementioning
confidence: 99%
“…Nontypeable Haemophilus influenzae (NTHI) migration from the nasopharynx to the upper and lower respiratory tract coincides with initiation of diseases such as otitis media (OM), conjunctivitis, sinusitis, and pneumonia, and exacerbates disease severity in patients with chronic obstructive pulmonary disease (COPD) and cystic fibrosis (Duell et al, 2016;Jalalvand and Riesbeck, 2018;Pelton, 2019;Romá n et al, 2004;Sriram et al, 2018). OM is the most common bacterial disease of children under 15 years of age, with 700 million cases of acute OM and 300 million cases of chronic suppurative OM each year (Mittal et al, 2015;Tong et al, 2018).…”
Section: Introductionmentioning
confidence: 99%